PENGARUH KOMPETENSI, MOTIVASI, DAN LINGKUNGAN KERJA FISIK TERHADAP KINERJA PEGAWAI PADA KANTOR DINAS ENERGI DAN SUMBER DAYA MINERAL KABUPATEN DONGGALA - Anggreany M., Andi Veny (Katalogis, 2017)
The purpose of this are: (1) to define the simultaneous influence of Competency, Motivation, and Physical Work Environment on the performance of Officials in the Departement of Energy and mineral Resources, Donggala Regency (2) to define the partial influence of Competency on the performance of Officials in the Departement of Energy and mineral Resources, Donggala Regency, (3) to define the partial influence of Motivation on the performance of Officials in the Departement of Energy and mineral Resources, Donggala Regency, (4) ) to define the partial influence of Physical Work Environment on the performance of Officials in the Departement of Energy and mineral Resources, Donggala Regency, Â Method of analysis used is multiple linear regressions with 51 samples that are selected throught census technique. Based on the tests, the study find Â that: 1) Competency, Motivation, and Physical Work Environment simultaneous have positive and significant influence on officials performance; 2) competency has positive and significant influence of officials performance; 3) motivation has positive and significant influence of officials performance; 4) Physical Work Environment has positive and significant influence of officials performance;